A comparative study of 4-chlorophenol biodegradation in a packed bed and moving bed bioreactor: Performance evaluation and toxicity analysis - Swain G.; Sonwani R.K.; Singh R.S.; Jaiswal R.P.; Rai B.N. (My University, 2025)
In this study, sponge-modified carrier, i.e., polypropylene–polyurethane​ foam (PP–PUF)was used in the bioreactors, namely moving bed bioreactor (MBBR) and packed bed bioreactor (PBBR), for the biodegradation of 4-CP. The Bacillus consortium isolated from the petroleum refinery site was used for the immobilization purpose. A comparative analysis was carried out to evaluate the performance of the MBBR and PBBR under identical conditions. The maximum removal efficiencies (REs) of 4-CP were obtained as 94.34 and 90.62 % in MBBR and PBBR, respectively, at an initial 4-CP concentration of 50 mg/L. Similarly, the chemical oxygen demand (COD) REs were found to be 83.26 and 79.37 % in MBBR and PBBR, respectively. The higher REs of 4-CP and COD were observed in MBBR due to the high growth of biomass. The total biomass found in the MBBR and PBBR was in the range of 1595–1752 mg/L and 1468–1640 mg/L, respectively. Andrew–Haldane model was more accurately predicted the growth inhibition of the Bacillus consortium compared to the Monod model. Moreover, the kinetic parameters were evaluated and found to be μmax: 0.19 h−1; Ks: 20.08 mg/L for Monod model, and μmax: 0.212 h−1; Ks: 7.05 mg/L; Ki: 163.67 mg/L for Andrew–Haldane model. The toxicity of the treated wastewater was evaluated using the Resazurin reduction method, and a maximum of 90 % toxicity removal was achieved in MBBR and PBBR up to 200 mg/L of 4-CP concentration. © 2021 Elsevier B.V.